AB0438 Chemokines and Renal Complications in Systemic Lupus Erythematosus. (15th July 2016) - Lee, C.P.; Yap, D.Y.H.; Li, P.H.; Chan, A.W.K.; Lee, L.H.; Chan, V.S.F.; Lau, C.S.
Abstract : Background: We and others have performed cluster analyses of patients with systemic lupus erythematosus (SLE) and revealed several prognostically distinct clinical patterns. Certain clusters of patients present with lupus nephritis (LN) while others remain LN free in the course of their disease. [1] This observation suggests different immunopathogenic mechanisms may be in play in the various disease manifestations of lupus. Chemokines recruit immune cells and have been proposed as biomarkers for LN. Objectives: This study aimed to investigate if changes in the serum levels of various chemokines were abnormal in patients with a clearly defined history of LN and non-LN (NLN). Chemokines, including interferon-γ-induced protein-10 (IP-10), RANTES and macrophage inflammatory protein-1α (MIP-1α) were examined. Methods: Patients were said to have LN if they had at least 1 episode of biopsy-confirmed Class III, IV or V (or any combination of these 3 classes) nephritis, while those who had not exhibited any renal diseases after at least 10 years of follow up were designated NLN. The LN patients were further divided into those with inactive LN (ILN) and active LN (ALN). ALN patients were recruited at the time of renal biopsy before immunosuppressive drug treatment. Enzyme-linked immunosorbent assay (ELISA) was used to measure the concentration of RANTES, MIP-1α and IP-10 in serum of the 3 groups of patients. Results: 80 patients were studied. 32 had ILN, 8 ALN and 40 NLN. Preliminary data show the serum levels of RANTES and MIP-1α were significantly lower in the LN group (including ALN and ILN) when compared with NLN SLE patients. (LN vs NLN: RANTES 3.3±5.7 ng/ml vs 7.6±9.9 ng/ml, p=0.0003; MIP-1α 39±106 pg/ml vs 86±158 pg/ml, p=0.03; IP-10 284±342 pg/ml vs 300±534 pg/ml, p=n.s.) There were no significant differences in the serum concentrations of RANTES and MIP-1α between the ALN and ILN subgroups (ALN vs ILN: RANTES 4.3±8.3 ng/ml vs 3.0±5.0ng/ml, p=n.s.; MIP-1α: 27±23 pg/ml vs 42±112 pg/ml, p=n.s.) For IP-10, no significant differences were found among the ILN, ALN and NLN groups. (ILN: 256±264pg/ml, ALN: 398±569pg/ml, NLN: 300±534pg/ml, all p =n.s.) Conclusions: LN patients had lower serum levels of RANTES and MIP-1α when compared with patients with clearly no LN disease. These chemokines may have an immunopathogenic role in the development of renal complications in SLE. That no differences in the serum levels of RANTES, MIP-1α and IP-10 were observed between ILN and ALN patients may suggest these chemokines are not implicated in LN disease progression although a larger cohort study with serial follow-up of patients before and after the development of LN and the use of immunosuppressive treatment is needed. This is underway. In addition, more candidate chemokines and related cytokines will be studied. References: Li, P.H., et al., Relationship between autoantibody clustering and clinical subsets in SLE: cluster and association analyses in Hong Kong Chinese. Rheumatology, 2013. 52(2): p. 337–345. Disclosure of Interest: None declared